Accuracy of device landing zone calcium volume measurement with contrast-enhanced multidetector computed tomography. (15th July 2018) - Kim, Won-Keun; Renker, Matthias; Rolf, Andreas; Liebetrau, Christoph; Van Linden, Arnaud; Arsalan, Mani; Doss, Mirko; Rieck, Julian; Opolski, Maksymilian P.; Möllmann, Helge; Walther, Thomas; Hamm, Christian W.
Abstract: Background: The extent of aortic valve calcification is an important determinant of procedural success in transcatheter aortic valve implantation (TAVI). We sought to validate device landing zone calcium volume (DLZ-CV) measurements on contrast-enhanced multidetector computed tomography (MDCT) with non-contrast-enhanced scans as reference. Methods: We determined DLZ-CV in 141 patients undergoing transfemoral TAVI. Non-contrast-enhanced images were analyzed using a threshold of 130 HU as reference (DLZ-CV130 ). For contrast-enhanced scans, we applied various thresholds including 450 HU (DLZ-CV450 ), 850 HU (DLZ-CV850 ), mean aortic attenuation (AttenAo ) + 2 SD (DLZ-CV2SD ), AttenAo + 4 SD (DLZ-CV4SD ), AttenAo + 4 SD + 5 mm 3 volume filter (DLZ-CV4SD+ ), and based on visual estimation (DLZ-CVvis ). We compared DLZ-CV values between patients with versus without paravalvular leak (PVL), and between patients with versus without post-dilatation stratified by the type of prosthesis. Results: All DLZ-CV measurements on contrast-enhanced scans significantly differed from DLZ-CV130 (p < 0.001 for all comparisons). The best approximation to DLZ-CV130 was achieved with DLZ-CV4SD+ (508 mm 3 [332–772]; Pearson correlation: R = 0.87, p < 0.001; Bland-Altman: mean difference 1339 mm 3 [limits of agreement 79;2600]). Moreover, DLZ-CV4SD+ allowed for discrimination of PVL ≥1° or the need for post-dilatation in patients receiving self-expanding prostheses. Procedural outcome using balloon-expandable prostheses was independent of DLZ-CV. Conclusion: Measurement of DLZ-CV using contrast-enhanced scans with unadjusted thresholds results in incorrect estimation of the calcium volume. The use of a scan-specific individual HU threshold including a volume filter (DLZ-CV4SD+ ) provides the best approximation to the reference and allows for discrimination of PVL ≥ 1° in patients receiving the Acurate neo prosthesis. Highlights: Measuring DLZ-CV on contrast-enhanced scans with unadjusted thresholds is inaccurate. Scan-specific individual HU-thresholds provide the best approximation to the Agatston method. DLZ-CV discriminates PVL ≥ 1° when using the self-expanding Acurate neo device. PVL is independent of DLZ-CV for the balloon-expandable Sapien 3 device.